Comparison of bedside assessed arm and leg fluid filtration determined by venous congestion plethysmography in perioperative cancer patients: An observational study investigating agreement. Issue 9 (March 2017) - Hunsicker, Oliver; Heinig, Sandra; Dathe, Jana-Jennifer; Krannich, Alexander; Spies, Claudia; Feldheiser, Aarne
Abstract : Abstract: In recent years, pathophysiology and clinical impact of microvascular fluid filtration has regained interest. As the latest data in surgical patients have been published almost 20 years ago, there is need for further research to better understand fluid filtration during the perioperative period. Venous congestion plethysmography (VCP) provides a rapid and noninvasive method, which has been shown suitable for the assessment of fluid filtration in limbs. Fluid filtration assessed by VCP can be obtained from forearm and calf measurement sites, while in many clinical situations a reduced access to the patient often restricts the measurements to patient's forearm. We aimed to investigate if fluid filtration obtained from forearm and calf measurement site is interchangeable in nonsedated perioperative patients. Fluid filtration by VCP was obtained simultaneously from forearm and calf in patients with ovarian cancer at 4 time points during the perioperative course and assessed by the difference of volume changes of the limb between third and sixth minutes (VC6-3min ) during venous congestion. VC6-3min obtained from forearm and calf measurement sites was compared with respect to agreement and evaluated regarding the association with the presence of leg edema. A total of 74 paired measurements were analyzed in 29 patients. Forearm VC6-3min was significantly higher than calf VC6-3min (median [25th; 75th quartile], 0.6 (0.4; 0.9) vs 0.4 [0.3; 0.6] %, P  = 0.008). Bland–Altman and Polar analysis revealed a poor agreement between forearm and calf VC6-3min at predefined time points and changes of VC6-3min during the perioperative course (bias +0.23%, limits of agreement [LOA] −1.1% to 1.6%; angular bias −2.5°, radial LOA −82° to +77°). Forearm VC6-3min was significantly increased in patients with presence of leg edema (0.7 (0.5; 1.0) vs 0.5 (0.4; 0.6) %, P  < 0.001) while calf VC6-3min did not differ in patients with and without edema. This study indicates that forearm and calf measurement sites are not interchangeable when bedside assessing fluid filtration by VCP in nonsedated perioperative patients. Considering that only forearm fluid filtration was related to the presence of edema, forearm measurement site should be chosen as a primary site for assessing fluid filtration.